The effect of nurses' preparedness and nurse practitioner status on triage call management in primary care: A secondary analysis of cross-sectional data from the ESTEEM trial. (June 2016) - Varley, Anna; Warren, Fiona C.; Richards, Suzanne H.; Calitri, Raff; Chaplin, Katherine; Fletcher, Emily; Holt, Tim A.; Lattimer, Valerie; Murdoch, Jamie; Richards, David A.; Campbell, John
Abstract: Background: Nurse-led telephone triage is increasingly used to manage demand for general practitioner consultations in UK general practice. Previous studies are equivocal about the relationship between clinical experience and the call outcomes of nurse triage. Most research is limited to investigating nurse telephone triage in out-of-hours settings. Objective: To investigate whether the professional characteristics of primary care nurses undertaking computer decision supported software telephone triage are related to call disposition. Design: Questionnaire survey of nurses delivering the nurse intervention arm of the ESTEEM trial, to capture role type (practice nurse or nurse practitioner), prescriber status, number of years' nursing experience, graduate status, previous experience of triage, and perceived preparedness for triage. Our main outcome was the proportion of triaged patients recommended for follow-up within the practice (call disposition), including all contact types (face-to-face, telephone or home visit), by a general practitioner or nurse. Settings: 15 general practices and 7012 patients receiving the nurse triage intervention in four regions of the UK. Participants: 45 nurse practitioners and practice nurse trained in the use of clinical decision support software. Methods: We investigated the associations between nursing characteristics and triage call disposition for patient 'same-day' appointment requests in general practice using multivariable logistic regression modelling. Results: Valid responses from 35 nurses (78%) from 14 practices: 31/35 (89%) had ≥10 years' experience with 24/35 (69%) having ≥20 years. Most patient contacts (3842/4605; 86%) were recommended for follow-up within the practice. Nurse practitioners were less likely to recommend patients for follow-up odds ratio 0.19, 95% confidence interval 0.07; 0.49 than practice nurses. Nurses who reported that their previous experience had prepared them less well for triage were more likely to recommend patients for follow-up (OR 3.17, 95% CI 1.18–5.55). Conclusion: Nurse characteristics were associated with disposition of triage calls to within practice follow-up. Nurse practitioners or those who reported feeling 'more prepared' for the role were more likely to manage the call definitively. Practices considering nurse triage should ensure that nurses transitioning into new roles feel adequately prepared. While standardised training is necessary, it may not be sufficient to ensure successful implementation.